2012
DOI: 10.1007/s12663-012-0420-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Pre-Emptive Analgesic Efficacy of Intramuscular Ketorolac Versus Tramadol Following Third Molar Surgery

Abstract: Pre-emptive analgesia aims at preventing the central nervous system from reaching a hyper-excitable state known as central sensitization, in which it responds excessively to afferent inputs. The clinical implication would be more effective pain management, thereby reducing post-operative pain and analgesic requirements. This study aimed at investigating the existence of preemptive analgesia and to compare the pre-emptive analgesic efficacy of im ketorolac [NSAID] versus tramadol [SYNTHETIC OPIOD] for post-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 13 publications
0
38
1
1
Order By: Relevance
“…Intramuscular Dexamethasone [10], diclofenac [18,27], ketorolac [18,30], tramadol [19,30,42,45], ketoprofen [27], meloxicam [42], 3.…”
mentioning
confidence: 99%
“…Intramuscular Dexamethasone [10], diclofenac [18,27], ketorolac [18,30], tramadol [19,30,42,45], ketoprofen [27], meloxicam [42], 3.…”
mentioning
confidence: 99%
“…However, its analgesic efficacy is controversial, with reports that its effect is similar [23] or less good [24] that of non-steroidal anti-inflammatory drugs (NSAID). According to these findings a single dose of tramadol has some relatively usual unfavorable effects [25]. The purpose of this study was to compare the outcome of preoperative administration of single-dose ketorolac, ibuprofen 400mg and placebo on postoperative pain in teeth with irreversible pulpitis and apical periodontitis.…”
mentioning
confidence: 99%
“…In addition, the author also found less cumulative opioid consumption in the study group patients treated with preemptive sublingual piroxicam. Shah et al 9 evaluated the analgesic efficacy of intramuscular ketorolac following the third molar surgery and concluded that prolonged duration of pain relief with intramuscular ketorolac signifies the existence of preemptive analgesia.…”
Section: Discussionmentioning
confidence: 99%